2020
DOI: 10.3390/met10060795
|View full text |Cite
|
Sign up to set email alerts
|

Laser Surface Hardening of Ni-hard White Cast Iron

Abstract: Laser surface treatment on two different types of nickel–chromium white cast iron (Ni-hard) alloys (Ni-hard 1 and Ni-hard 4) was investigated. Nd:YAG laser of 2.2-kw with continuous wave was used. Ni-hard alloys are promising engineering materials, which are extensively used in applications where good resistance to abrasion wear is essential. The conventional hardening of such alloys leads to high wear resistance nevertheless, the core of the alloy suffers from low toughness. Therefore, it would be beneficial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
(41 reference statements)
1
3
0
Order By: Relevance
“…From Figure 4, can be observed that the depth of the hardened region was inversely proportional to the scan speed of the laser beam, the depth of the hardened region slightly increased as scan speed decreased at a certain laser power, and became clearer with increasing laser power, the reason for this when the scan speed decreases, the heating time increases, thereby increase the heat input, which increases the depth of the hardened region. This result agrees with what was obtained by Samar Reda Al-Sayed et al [12] Figure 3: Microhardness with different power…”
Section: Effect Of Laser Processes On Hardeningsupporting
confidence: 92%
See 1 more Smart Citation
“…From Figure 4, can be observed that the depth of the hardened region was inversely proportional to the scan speed of the laser beam, the depth of the hardened region slightly increased as scan speed decreased at a certain laser power, and became clearer with increasing laser power, the reason for this when the scan speed decreases, the heating time increases, thereby increase the heat input, which increases the depth of the hardened region. This result agrees with what was obtained by Samar Reda Al-Sayed et al [12] Figure 3: Microhardness with different power…”
Section: Effect Of Laser Processes On Hardeningsupporting
confidence: 92%
“…the technology of surface treatment is one of the key approaches for creating materials with improved mechanical qualities. Surface treatments are commonly used to enhance the surface properties of alloys and materials such as hardness, corrosion and wear resistance, to achieve high-performance requirements of industrial applications [10]- [12].…”
Section: Introductionmentioning
confidence: 99%
“…Laser surface engineering is a novel approach for the surface modification of metals that are aimed at enhancing their performance when subjected to severe environmental and industrial conditions [ 11 ]. Laser processing, which is a newly developed technique, offers many attractive advantages over conventional coating techniques [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…DED system consists of 9-axis numerical control working table and an attached coaxial nozzle powder feeder system (TECHNOGENIA Middle East company, Dubai, UAE). During the DED process, TC21 sample was placed in an area protected by argon gas that was continuously shielded with a flowing rate of 15 L min −1 to avoid any oxidation of the melt pool [20,21]. To investigate the influence of DED process parameters on quality characteristics and microhardness of deposited layer, a series of powder feeding rates were attempted as listed in Table 1.…”
Section: Design Of Ded Experimentsmentioning
confidence: 99%